2020
DOI: 10.1155/2020/3908641
|View full text |Cite
|
Sign up to set email alerts
|

Heat Shock Protein 70 Protects the Heart from Ischemia/Reperfusion Injury through Inhibition of p38 MAPK Signaling

Abstract: Background. Heat shock protein 70 (Hsp70) has been shown to exert cardioprotection. Intracellular calcium ([Ca2+]i) overload induced by p38 mitogen-activated protein kinase (p38 MAPK) activation contributes to cardiac ischemia/reperfusion (I/R) injury. However, whether Hsp70 interacts with p38 MAPK signaling is unclear. Therefore, this study investigated the regulation of p38 MAPK by Hsp70 in I/R-induced cardiac injury. Methods. Neonatal rat cardiomyocytes were subjected to oxygen-glucose deprivation for 6 h f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 52 publications
0
34
0
Order By: Relevance
“…The rat myocardial I/R injury model was established as previously described. 22 , 24 Rats were anesthetized with intraperitoneal sodium pentobarbital 50 mg/kg. After tracheal intubation, the lungs were ventilated with room air, tidal volume 20 mL/kg, 1:1 ratio, and 70 breaths/min, by using an animal ventilator (R407, RWD, Shenzhen, China).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The rat myocardial I/R injury model was established as previously described. 22 , 24 Rats were anesthetized with intraperitoneal sodium pentobarbital 50 mg/kg. After tracheal intubation, the lungs were ventilated with room air, tidal volume 20 mL/kg, 1:1 ratio, and 70 breaths/min, by using an animal ventilator (R407, RWD, Shenzhen, China).…”
Section: Methodsmentioning
confidence: 99%
“…H9c2 cardiomyocytes were treated with glucose-free DMEM and incubated in a hypoxia chamber with 95% N 2 and 5% CO 2 at 37 °C, as previously described. 23 , 24 The cells were subjected to OGD for 12 h, followed by reoxygenation for 3 h with the normal DMEM under a normoxia condition.…”
Section: Methodsmentioning
confidence: 99%
“…Song et al indicated that rat cardiomyocytes subjected to oxygen-glucose deprivation/reperfusion showed increased expression of HSP70 and p-p38 MAPK; the same observation applies to increased HSP70 expression and phosphorylated p38 MAPK during I/R-induced myocardial injury, and inhibition of HSP70 by quercetin significantly increased myocardial infarct size [ 85 ]. It is very important that HSP70 inhibition led to upregulation of p-p38 MAPK and p-STAT3 and downregulation of SERCA2 (sarco/endoplasmic reticulum Ca 2+ -ATPase) during myocardial I/R injury, and inhibition of p38 MAPK phosphorylation attenuated effects induced by HSP70 inhibition [ 85 ]. In contrast to inhibition of HSP90, inhibition of HSP70 aggravates [Ca 2+ ] i overload, apoptosis, and inflammation through regulating p38 MAPK signaling during I/R cardiac injury.…”
Section: Heat Shock Proteins In Ischemia/reperfusion Injurymentioning
confidence: 99%
“…p38 inhibition during ischemia–reperfusion decreases mitochondrial swelling, protects against ultra-structure alterations, and mitigates mitochondrial membrane depolarization [ 78 ]. There is also evidence that p38 activation during ischemia–reperfusion contributes to cardiac damage by triggering intracellular Ca 2+ overload [ 79 ]. Pharmacological inhibition of p38 during ischemia–reperfusion induces cardioprotection by promoting phospholamban phosphorylation, increasing the activity of sarcoplasmic reticulum Ca 2+ -ATPase (SERCA2), and decreasing Ca 2+ overload [ 80 ].…”
Section: P38 In Ischemia–reperfusion Injurymentioning
confidence: 99%